2020
DOI: 10.1186/s12879-020-05062-y
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of dengue shock syndrome complicated by ilio-femoral deep vein thrombosis; a case report

Abstract: Background: Dengue fever is a hemorrhagic fever caused by flaviviruses. Hemorrhagic manifestations are well known to be associated with dengue fever, though the thrombotic events are only seldom reported. Underlying pathophysiology of thrombotic events is multifactorial and the management is challenging due to associated thrombocytopenia and bleeding tendency. We report a case of dengue shock syndrome with severe thrombocytopenia complicated by ilio-femoral deep vein thrombosis. Case presentation: A 16 year ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Platelets exhaustion/clearance is a possible mechanism since it is likely that platelets are hyper-activated in the initial stage of COVID-19 disease and then become hyporeactive in the later stages. Noteworthy, also in some cases of dengue fever infection a prothrombotic status was described in the initial stage of the infection [ 10 ]. Another mechanism leading to reduced platelet aggregation may rely on higher concentrations of VWF, which may bind to platelet receptor for fibrinogen thus reducing aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets exhaustion/clearance is a possible mechanism since it is likely that platelets are hyper-activated in the initial stage of COVID-19 disease and then become hyporeactive in the later stages. Noteworthy, also in some cases of dengue fever infection a prothrombotic status was described in the initial stage of the infection [ 10 ]. Another mechanism leading to reduced platelet aggregation may rely on higher concentrations of VWF, which may bind to platelet receptor for fibrinogen thus reducing aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Da Costa et al reported an incidence of 5.4% thrombotic events in patients with severe dengue with a total of 5 venous thrombotic events, 4 of the cases were DVT and 1 mesenteric venous thrombosis; nonetheless, it was not an isolated event since concomitantly Escherichia coli bacteremia, a well-known risk factor for portal vein thrombosis, was diagnosed [ 4 ]. Other thrombotic events associated with dengue described in the literature are mainly cerebral venous thrombosis and DVT; in many of these cases, an associated procoagulant factor was not found either [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of the disease can range from mild symptoms to more severe but infrequent manifestations such as septic shock and coagulation disorders [3], where hemorrhagic events predominate. Cases of thrombosis are exceptional and only a few have been reported in the literature [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The network-based analysis suggested that 3 drugs have repurposable properties: aspirin, captopril, and rilonacept; however, because of their anticoagulant qualities, patients should be encouraged to be properly hydrated and avoid aspirin (ie, acetylsalicylic acid), aspirin-containing medicines, and other nonsteroidal anti-inflammatory drugs, such as ibuprofen [30]. On the other hand, several studies have reported that thrombosis is associated with dengue fever [32,33]; hence, further studies are essential to prove the efficiency of aspirin and the other repurposed drugs identified in this study for the treatment of DHF.…”
Section: Comparison To Prior Workmentioning
confidence: 99%